Role of Cysteine Residues in the Carboxyl-Terminus of the Follicle-Stimulating Hormone Receptor in Intracellular Traffic and Postendocytic Processing - Melo-Nava, Brenda; Casas-González, Patricia; Pérez-Solís, Marco A.; Castillo-Badillo, Jean; Maravillas-Montero, José L.; Jardón-Valadez, Eduardo; Zariñán, Teresa; Aguilar-Rojas, Arturo; Gallay, Nathalie; Reiter, Eric; Ulloa-Aguirre, Alfredo (Frontiers in Cell and Developmental Biology, 2016)
Posttranslational modifications occurring during the biosynthesis of G protein-coupled receptors include glycosylation and palmitoylation at conserved cysteine residues located in the carboxyl-terminus (Ctail) of the receptor. In a number of these receptors, these modifications play an important role in receptor function and particularly, in intracellular trafficking. In the present study, the three cysteine residues present in the carboxyl-terminus of the human FSHR were replaced with glycine by site-directed mutagenesis. Wild-type and mutant (Cys627/629/655Gly) FSHRs were then transiently expressed in HEK-293 cells and analyzed for cell-surface plasma membrane expression, agonist-stimulated signaling and internalization, and postendocytic processing in the abscence and presence of lysosome and/or proteasome inhibitors. Compared with the wild-type FSHR, the triple mutant FSHR exhibited ~70% reduction in plasma membrane expression as well as a profound attenuation in agonist-stimulated cAMP production and ERK1/2 phosphorylation. Incubation of HEK-293 cells expressing the wild-type FSHR with 2-bromopalmitate (palmitoylation inhibitor) for 6 h, decreased plasma membrane expression of the receptor by ~30%. The internalization kinetics and β-arrestin 1 and 2 recruitment were similar between the wild-type and triple mutant FSHR as disclosed by assays performed in non-equilibrium binding conditions and by confocal microscopy. Cells expressing the mutant FSHR recycled the internalized FSHR back to the plasma membrane less efficiently than those expressing the wild-type FSHR, an effect that was counteracted by proteasome but not by lysosome inhibition. These results indicate that replacement of the cysteine residues present in the carboxyl-terminus of the FSHR, impairs receptor trafficking from the endoplasmic reticulum/Golgi apparatus to the plasma membrane and its recycling from endosomes back to the cell surface following agonist-induced internalization. Since in the FSHR these cysteine residues are S-palmitoylated, the data presented emphasize on this posttranslational modification as an important factor for both upward and downward trafficking of this receptor.